HOLISTIC TAX OPTIMIZATION: INTEGRATING LEGAL, FINANCIAL, AND STRATEGIC APPROACHES FOR INDIVIDUALS AND BUSINESSES - Shohib Muslim; Ahmad Rizani; Rio Era Deka; Pratiwi Subianto; Iyad Abdallah Al- Shreifeen (Adisam Publisher, 2023)
Tax optimization, a multifaceted challenge in today's dynamic economic landscape, requires a comprehensive and integrated approach for individuals and businesses. This paper delves into the intricate dynamics of holistic tax optimization, spotlighting the fusion of legal, financial, and strategic methodologies. By examining diverse strategies and their consequential impacts, the research offers a nuanced understanding of how a unified approach can produce superior outcomes when navigating taxation complexities. This study employs a mixed-methods approach, combining quantitative analyses, case studies, and qualitative insights from expert interviews and literature reviews. The results underscore the effectiveness of a holistic strategy, wherein legal compliance establishes a robust foundation, financial planning maximizes available incentives, and strategic alignment positions entities for sustained success. The discussion section explores the challenges and opportunities inherent in implementing holistic strategies, addressing regulatory changes, and market dynamics. In conclusion, this paper advocates for a paradigm shift towards an integrated approach to taxation, contributing to the discourse on effective tax planning in the modern era.